Experimental and theoretical approach: Chemical activity, charge transfer of DNA/ECT, thermodinamic, spectroscopic, structural and electronic properties of N-(4-(3-methyl-3-phenylcyclobutyl)thiazol-2-yl)acetamide molecule - Ekici, Oner; Demircioglu, Zeynep; Ersanli, Cem Cuneyt; Cukurovali, Alaaddin (Elsevier, 2020)
N-(4-(3-methyl-3-phenylcyclobutyl)thiazol-2-yl)acetamide compound was synthesized and characterized by using FT-IR, UV-Vis, NMR and X-ray diffraction techniques. The title compound crystallizes in monoclinic space group P2(1)/c with four molecules in the unit cell and unit cell dimensions are a = 15.590(3) angstrom, b = 9.1348(15) angstrom and c = 11.035(2) angstrom. Hirshfeld surface (HS) analysis reveals the nature of intermolecular contacts, the fingerprint plots and molecular surface contours. All theoretical computations were calculated by using density functional theory (DFT) B3LYP method with the help of 6-311++G(d,p) basis set. The global (FMOs, hardness and softness parameters) and local (MEP, FF, net charges) chemical activity descriptors were investigated and the results indicated that the optimized structure is more electrophilic nature than nucleophilic one. According to ECT (electrophilicity-based charge transfer) method and Delta N (charge transfer) results, the electrons were transferred from the DNA bases of adenine to title molecule. Therefore, the adenine treated as the electron donor and the title molecule as the electron acceptor. The other DNA bases of cytosine, guanine, and thymine bases showed electrophilic nature and electrons were transferred from title molecule to these DNA bases. The stability of the molecule arising from hyperconjugative interactions, charge delocalization was analyzed by using natural bond orbital analysis (NBO). The thermodynamic properties of the title compound at different temperatures have been calculated, and corresponding relations between the properties and temperature have also been obtained. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: X-ray diffraction method; HS analysis; Chemical activity; DNA/ECT charge transfer